Association of vision and hearing status with depressive symptoms among middle-aged and older Chinese adults - Yun-Guang Liu; Chao-Cai Wang; Qian Huang; Le Zhang; Yan Liu (Frontiers Media S.A., 2022)
ObjectiveLong-term untreated vision and hearing impairments can negatively impact physical and mental wellbeing. We investigated the association of vision and hearing status with depressive symptoms among middle-aged and older Chinese adults.Methods:This was a prospective cohort study of 9,492 participants from the China Health and Retirement Longitudinal Study (CHARLS) carried out in 2011, 2013, 2015, and 2018. This study used self-reported vision and hearing status to determine the degree of impairment. Depressive symptoms were examined using the 10-item Center for Epidemiologic Studies Depression Scale (CESD-10), with a total score of ≥ 12 indicating depressive symptoms. A Cox proportional hazards model adjusted for age, sex, residence, marital status, educational level, smoking history, alcohol consumption, hypertension, diabetes, heart disease, digestive disease, arthritis, wearing glasses, and hearing aids was used to estimate the association of vision and hearing status with depressive symptoms among middle-aged and older Chinese adults.Results:Of the 9,492 participants [mean (SD) age at CHARLS baseline, 58.12 (9.00) years], 3,238 (34.11%) participants reported incident depressive symptoms during the 7-year follow-up period. Participants who self-reported only vision impairment [hazard ratios (HR): 1.14, 95% confidence intervals (CI): 1.05-1.24], only hearing impairment (HR: 1.24, 95% CI: 1.06-1.46), and both vision and hearing impairments (HR: 1.25, 95% CI: 1.08-1.45) were independently associated with a greater increase in the hazard risk of incident depressive symptoms compared to those without vision and hearing impairments. An increase in participants' vision and hearing scores was associated with a significant increase in the hazard risk of incident depressive symptoms (HR: 1.04, 95% CI: 1.03-1.06).Conclusion:Vision and hearing status was associated with increased depressive symptoms among middle-aged and older Chinese adults during the 7-year follow-up period. Participants' use of glasses and hearing aids did not improve their depressive symptoms. Our findings may facilitate the development of effective treatments to prevent and treat vision and hearing impairments, thereby enhancing the physical and mental wellbeing of middle-aged and older adults.